(Fx)'=F'x+Fx'
(ΔFx/Δt)=(ΔF/Δt)x+F(Δx/Δt)
(Fx)'=F'x+Fv
(Fx)'-F'x=Fv
Fv=(Fx)'-F'x
(-Fv)=-(Fx)'+F'x
(Fx)'=F'x+Fx'
(ΔFx/Δt)=(ΔF/Δt)x+F(Δx/Δt)
(ΔFx/Δt)=F'x+Fv
ΔFx/Δt=F'x+Fv
ΔFx=F'xΔt+FvΔt
ΣΔFx=ΣF'xΔt+ΣFvΔt
Fx=ΣF'xΔt+ΣFvΔt
(Fx)'=F'x+Fx'
(Fx)'-F'x=Fx'
(ΔFx/Δt)-(ΔF/Δt)x=F(Δx/Δt)
(Fx)'-F'x=Fv
Fv=(Fx)'-F'x
(-Fv)=-(Fx)'+F'x
(Fx)'=F'x+Fx'
(Fx)'-F'x=Fx'
(ΔFx/Δt)-(ΔF/Δt)x=F(Δx/Δt)
(ΔFx/Δt)-F'x=Fv
ΔFx/Δt-F'x=Fv
Fv=ΔFx/Δt-F'x
FvΔt=ΔFx-F'xΔt
ΣFvΔt=ΣΔFx-ΣF'xΔt
ΣFvΔt=Fx-ΣF'xΔt
(Fx)'=F'x+Fx'
(Fx)'-F'x=Fx'
Fx'=(Fx)'-F'x
F(Δx/Δt)=(ΔFx/Δt)-(ΔF/Δt)x
Fv=(Fx)'-F'x
(-Fv)=-(Fx)'+F'x
(Fx)'=F'x+Fx'
(Fx)'-F'x=Fx'
Fx'=(Fx)'-F'x
F(Δx/Δt)=(ΔFx/Δt)-(ΔF/Δt)x
Fv=(ΔFx/Δt)-F'x
FvΔt=ΔFx-F'xΔt
ΣFvΔt=ΣΔFx-ΣF'xΔt
ΣFvΔt=Fx-ΣF'xΔt
(mvv)'=mv'v+mvv'
Δmvv/Δt=m(Δv/Δt)v+mv(Δv/Δt)
(mvv)'=mav+mva
(mvv)'=mav+mav
(mvv)'=2mav
(mvv)'=2Fv
2Fv=(mvv)'
Fv=(1/2)(mvv)'
(-Fv)=(-1/2)(mvv)'
コメント
最新を表示する
NG表示方式
NGID一覧